Comparison of Learning Outcomes at Homeschooling Pena Surabaya: Private Home-visit, Distance Learning, and Community Class - Elfiana, Dwi Endah; Agustin, Putri Nanda; Nurul Mufida, Shobrina; Asih, Tri Lestari Budi; Khotimah, Khusnul (Spectrum of Science Education Research and Application, 2024)
This study examines the differences in learning outcomes of students participating in different learning groups at Homeschooling Pena Surabaya: private home-visit learning, distance learning (group online learning), and community classes (group learning at school). The purpose of this research is to compare the learning outcomes of students using each teaching method. The data used in this study are students' academic grades from the three learning groups. The data were analyzed using one-way ANOVA. The results of the data analysis show that there is no significant difference in learning outcomes among the three learning groups. This study provides insights into the advantages and disadvantages of each learning method and offers practical recommendations for parents, teachers, and homeschooling administrators. The implications of these findings are expected to aid in developing better educational practices and support alternative education in Indonesia